2018
DOI: 10.1371/journal.pone.0197874
|View full text |Cite|
|
Sign up to set email alerts
|

Examining food intake and eating out of home patterns among university students

Abstract: Eating out of home (OH) is increasingly popular in Balkan countries, among them Albania. To date there is only anecdotal evidence regarding nutritional quality of food consumed OH and the contribution to diet. This study assessed intake of foods and drinks consumed OH and at home (AH), as well as their nutritional contribution to the daily diet of university students in Tirana, Albania. Using a single day Automated Multiple Pass Method (AMPM) 24-hour dietary recall, we examined food intake among 289 students a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 34 publications
5
50
1
2
Order By: Relevance
“…A systematic review aimed to study the association with dietary intake eating out of home, concluded that eating out of home contributes to a higher intake of fats, particularly saturated fats in the daily diet especially in adults [33]. Llanaj et al [34] reported a higher intake of foods that do not fit the traditional MedDiet such as sweets, soft drinks and meat products and a low consumption of fruits and vegetables among undergraduate students who used to eat out of home.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review aimed to study the association with dietary intake eating out of home, concluded that eating out of home contributes to a higher intake of fats, particularly saturated fats in the daily diet especially in adults [33]. Llanaj et al [34] reported a higher intake of foods that do not fit the traditional MedDiet such as sweets, soft drinks and meat products and a low consumption of fruits and vegetables among undergraduate students who used to eat out of home.…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary analysis of observational data from a cross-sectional epidemiological study conducted between October 2015 and February 2016 in Tirana, Albania (35) .…”
Section: Methodsmentioning
confidence: 99%
“…The growing presence of eating out of home in the Western diet [2,3] could reflect changes in both the demand of consumers and the approach of food providers, thereby affecting the nutritional quality of food and, consequently, consumer health. Given that commercially processed food products and restaurant foods contribute substantially to meat [4] and dietary salt intake [5,6], developing healthy meals, which are plant-based and low in salt content, is a major challenge for the food industry and restaurant sector due to its impact on foods' sensory profile and consumer acceptance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Kristensen et al [34] showed that protein-rich meals based on beans and peas increased satiety more than protein-rich veal and pork-based meals. Meat is among the most popular choices in eating out of home [4] and, with more and more people choosing to eat away from home [35], the more traditional "full-service" restaurant sector contributes significantly to the out-of-home dining market [36]. In this setting, using herbs and spices to enhance liking of legumes while compensating for reduction of salt in a real context ecological restaurant is an area of research that needs further attention.…”
Section: Introductionmentioning
confidence: 99%